PERDA Baca Tulis Al-Quran: Studi terhadap Respon Wali Nagari dalam Meningkatkan Pendidikan Agama di Talu - Ronaldi Ronaldi; Ahmad Lahmi; Mursal Mursal (UMSU, 2020)
The local government has the authority to take policy, as has the Regent of West Pasaman period 2007 has taken policies related to improving the reading ability of the Qur'an for every child in the government area he leads. This research will trace how the regent responded in enforcing perda No. 9 year 2007 so as to give birth to a generation that is able to read the Qur'an well and have sufficient religious understanding. The design of this study is qualitative, while the data sources that researchers use are nagari guardians, purposively selected citizens, community leaders, according to the desired data then in this study used data collection techniques in the form of observations, interviews and documentation studies. The results of the study prove that: first, Wali Nagari has a positive response, the indicator is the instruction of the guardian agari to all citizens to submit their children to the mosque and mushalla to get a reading education writing the Qur'an, renovate the mosque and mushalla to be worthy as a place to learn to read the Qur'an, complete the necessary facilities, give appreciation to the teachers paying in every mosque and mushalla that is in Talu nagari. Second, children's understanding of Islamic religious education has increased since the regulation of the area was established.